PERANCANGAN SISTEM INFORMASI PENDAFTARAN RAWAT JALAN PASIEN RSKIA ADINDA BERBASIS WEBSITE - Febrianti Pustaria Anggraini; Paulus Tofan Rapiyanta - Universitas Bina Sarana Informatika (Indonesian Journal of Networking and Security (IJNS), 2022)
Abstract - RSKIA Adinda is a Special Hospital for Mother and Child Adinda which is one of the private maternity hospitals in the Bantul region of Yogyakarta. The problem that has occurred at RSKIA Adinda so far is that the management of patient registration data is still manual. The purpose of this final project is to find out the flow and process of the registration system, design a registration information system and analyze the website-based registration system at RSKIA Adinda. For this research, the author uses a prototyping method with a research flow starting from gathering requirements needed, processing the design fast, prototyping design, conducting evaluation and making the improvement. For the data collection technique, the author uses is the interview method, the method of observation, documentation and literature study. The final project concludes that the offline registration system requires transportation costs, patient registration by telephone requires credit and registration by google forms causes data to be out of sync and double registration data. Finally, the suggestions that the authors could give are patient registration is better to use a computerized system, update information regularly and routinely, provide adequate hardware support, add human resources, and use back-up file systems. Keywords - Design, Information System, Patient Registration, Outpatient, Website Abstrak - RSKIA Adinda merupakan Rumah Sakit Khusus Ibu dan Anak Adinda yang menjadi salah satu rumah sakit bersalin swasta di wilayah Bantul Yogyakarta. Permasalahan yang terjadi di RSKIA Adinda selama ini adalah pengelolaan data pendaftaran pasien masih secara manual. Tujuan dari tugas akhir ini adalah untuk mengetahui alur dan proses sistem pendaftaran, merancang sistem informasi pendaftaran pasien dan menganalisis sistem pendaftaran pasien berbasis website di RSKIA Adinda. Metode yang penulis gunakan adalah menggunakan metode prototyping dengan alur penelitian mulai dari pengumpulan kebutuhan, proses desain secara cepat, perancangan prototyping dan evaluasi hingga perbaikan. Teknik pengumpulan data yang digunakan penulis adalah metode wawancara, metode pengamatan atau observasi, dokumentasi dan studi pustaka. Kesimpulan dari tugas akhir yang penulis tulis adalah sistem pendaftaran yang berjalan offline membutuhkan biaya transportasi, pendaftaran pasien via telfon memakan pulsa dan pendaftaran via google form menyebabkan ketidak sinkronan data sekaligus double data pendaftaran. Saran yang penulis berikan adalah pendaftaran pasien dengan menggunakan sistem terkomputerisasi, up to date informasi secara berkala dan rutin, dukungan hardware yang memadai, penambahan sumber daya manusia, back up file sistem. Kata Kunci: Perancangan, Sistem Informasi, Pendaftaran Pasien, Rawat Jalan, website.